Jim Rochford interviewed by Matthew Higgins for the Canberra region oral history project - Rochford, James A.; Higgins, Matthew, 1957- (1991)
Rochford provides a description of various aspects of life in the Hall district during the early part of the twentieth century.
Recorded on 5 Sept. 1991 in Hall, A.C.T.
Digital master available
Timed summary and transcript (typescript, 194 leaves) available.
Keywords: Rochford, James A. -- Interviews; Hall (A.C.T.) -- History